The Determinants of Dividend Policy in the Consumer Goods Industry Listed on the Indonesia Stock Exchange - Rinaldy Achmad Roberth Fathoni; Warsono (Manajemen Bisnis, 2023)
The purpose of this research is to understand and conduct empirical research to determine whether profitability variables, company size, liquidity, institutional ownership level, and leverage are determinants of dividend policy in consumer goods companies listed on the Indonesia Stock Exchange. This research is conducted due to issues found in previous research results, which indicated that among the explanatory variables, some have a positive, negative, or even no significant impact on dividend policy. The research population consists of all consumer goods companies, totaling 65 companies listed on the Indonesia Stock Exchange. The sampling technique employed is judgment sampling, with 12 companies selected as the sample. The results of the data analysis conclude that among the five explanatory variables, only two determinant variables significantly affect dividend policy, namely profitability and institutional ownership. Among profitability and institutional ownership variables, it turns out that profitability has a greater impact on dividend policy.